Social Interaction of Kindergarten Children (The International Journal of Educational Sciences and Arts, 2023)
Human beings are social creatures, and their existence is tied to their interactions with others, whether these interactions are positive or negative. One can devote much of their life to helping others, or live selfishly and prioritize their personal interests. Social interaction in any society is influenced by the psychological, social, and political conditions that the society experiences. The more a climate of warmth, empathy, and stability prevails, the more positive the relationships between individuals will be, and the opposite leads to negative relationships. Today, our Iraqi society needs social cohesion and positive relationships between its members more than ever, due to the unjust economic blockade that the country suffers from, which has led to negative behavior and attitudes among its youth. Ethics are the guardian of the individual and the foundation of a civilized society. It is not enough for the teacher to guide individuals on virtues, as a good education requires a long process of continuous commitment, and depends largely on a good family environment. The current research aims to identify the aspects of social interaction among preschool children and to clarify the importance of social interaction. Children begin interacting from the earliest days of their lives, and this interaction grows until the preschool stage, where they acquire the ability to communicate effectively.
Keywords: Social interaction; social relationships; social interaction skills; social stability; kindergarten children